Implementation of Medical Genetics in Medical Education Curriculum - Teguh Aryandono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Primary care physicians should be aware that genomics has arrived at the doorstep of their practice. Genetic knowledge, skills, and attitudes are important to primary care physicians providing support and management to patients and families with (higher risks of) genetic conditions. At least one in ten patients seen in primary care has a disorder with a genetic component, including hereditary cancer.Primary care physicians must be able to advise patients on genetic and genomic manifestations of the associated diseases and disorders, to outline a primary pedigree to deliver the necessary information: the disease which the patients are at risk of, and to decide whether to refer the patients to genetic services.There is more and more evidence to the importance of clinical emphasis in the genetics classes, probably proceeding to a third-year refresher program in the longitudinal curriculum. An enhanced educational experience to improve genetics and genomics knowledge should be better structured in the imminent future.Keywords: primary care physicians, hereditary cancer, genetic curriculum, genetic services